CT Angiography Manual Multiplanar Vessel Diameter Measurement vs. Semiautomated Perpendicular Area Minimal Caliber Computation of Internal Carotid Artery Stenosis - Siepmann, Timo; Barlinn, Kristian; Floegel, Thomas; Barlinn, Jessica; Pallesen, Lars-Peder; Puetz, Volker; Kitzler, Hagen H. (Frontiers in Cardiovascular Medicine, 2021)
Objective: To determine diagnostic agreement of CT-angiography (CTA) manual multiplanar reformatting (MPR) stenosis diameter measurement and semi-automated perpendicular stenosis area minimal caliber computation of extracranial internal carotid artery (ICA) stenosis. Methods: We analyzed acute cerebral ischemia CTA at our tertiary stroke center in a 12-months period. Prospective NASCET–type stenosis grading for each ICA was independently performed using (1) MPR to manually determine diameters and (2) perpendicular stenosis area with minimal caliber semi-automated computation to grade luminal constriction. Corresponding to clinically relevant NASCET strata, results were grouped into severity ranges: normal, 1-49%, 50-69%, 70- 99%, and occlusion. Results: We included 647 ICA pairs from 330 patients (median age 74 [66-80, IQR]; 38-92 years; 58% male; median NIHSS 4 [1-9, IQR]. MPR diameter and semi-automated caliber measurements resulted in stenosis grades of 0-49% in 143 vs 93, 50-69% in 29 vs 27, 70-99% in 6 vs 14, and, occlusion in 34 vs 34 ICAs (p=0.003), respectively. We found excellent reliability between between repeated manual CTA assessments of one expert reader (ICC =0.997; 95%CI, 0.993-0.999) and between assessments of two expert readers (ICC=0.972; 95%CI, 0.936-0.988). For the semi-automated vessel analysis software, both intra- and inter-rater-reliability were similarly strong (ICC=0.981; 95%CI, 0.952-0.992 and ICC =0.745;95%CI, 0.486-0.883, respectively). However, Bland-Altman analysis revealed a mean difference of 1.6% between the methods within disease range with wide 95% limits of agreement (-16.7 to 19.8%). This interval even increased with exclusively considered vessel pairs of stenosis ≥1% (mean 5.3%; -24.1 to 34.7%) or symptomatic stenosis ≥50% (mean 0.1%; -25.7 to 26.0). Conclusion: Our findings suggest that MPR based diameter measurement and the semi-automated perpendicular area minimal caliber computation methods cannot be used interchangeably for the quantification of ICA steno-occlusive disease.